2022
DOI: 10.4018/ijcallt.315306
|View full text |Cite
|
Sign up to set email alerts
|

Examining EFL Teachers' TPACK Perceptions, Web 2.0 Tools Usage, Workload, and Technostress Levels

Abstract: This study was conducted to examine English teachers' TPACK perceptions in light of web 2.0 tools usage, workload, and technostress levels. The participants were 170 English teachers and the data were collected using snowball sampling and analyzed by applying MANOVA, and Multiple Regression with descriptive analyses. The results revealed that English teachers have positive TPACK perceptions with a moderate level of technostress and workload and they use web 2.0 tools, although not very often. Considering TPACK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 70 publications
1
1
0
Order By: Relevance
“…Participants have strong belief (M=4.35) that digital tools and resources may support their professional development, and this is supported by Lee et al (2023), reported technology impacted teacher continuous professional development in their research study. Participants' perception on their ability to use Web 2.0 tools obtained the lowest mean score (M= 4.04) in the TPACK subdomain, this result is align with Hunutlu & Kucuk (2022) research, which reported that although English teachers have positive perceptions of TPACK, it appears that they do not often employ web 2.0 tools.…”
Section: Technological Pedagogical and Content Knowledge (Tpapk)supporting
confidence: 86%
“…Participants have strong belief (M=4.35) that digital tools and resources may support their professional development, and this is supported by Lee et al (2023), reported technology impacted teacher continuous professional development in their research study. Participants' perception on their ability to use Web 2.0 tools obtained the lowest mean score (M= 4.04) in the TPACK subdomain, this result is align with Hunutlu & Kucuk (2022) research, which reported that although English teachers have positive perceptions of TPACK, it appears that they do not often employ web 2.0 tools.…”
Section: Technological Pedagogical and Content Knowledge (Tpapk)supporting
confidence: 86%
“…The Standards of Educational Technology Competence of Primary and Secondary School Teachers in China also put forward: "The profession of teachers tends to be specialized, and the standard to measure the professional specialization of teachers is the level of teachers' intelligent intelligent information technology level, especially in the special aspects of education [8][9][10][11]." Biological experiments are an indispensable part of students' biology learning, and biology and social life are inextricably linked.…”
Section: Introductionmentioning
confidence: 99%